On language change : the invisible hand in language - Keller, Rudi (Routledge, 1994)
"In the twentieth century, linguistics has been dominated by two paradigms - those of Saussure and Chomsky. In both these philosophies of linguistics, language change was left aside as an unsolvable mystery which challenged theoretical entirety." "In On Language Change Rudi Keller reassesses language change and places it firmly back on the linguistics agenda. Based on the ideas of eighteenth- and nineteenth-century thinkers such as Mandeville, Smith and Menger, he demonstrates that language change can indeed be explained through the workings of an 'invisible hand'." "Refreshingly jargon-free, Keller's account of language change is comprehensive and clear. Not only does he provide a new epistemology for the science of language change, he also brings new insights to bear on the history of linguistics."--Jacket